2017
DOI: 10.14260/jemds/2017/4
|View full text |Cite
|
Sign up to set email alerts
|

Does Birth Weight Influence the Age of Menarche? A Cross Sectional Study in Rural Kerala

Abstract: BACKGROUNDAge of menarche is showing a declining trend in all parts of the world. The reasons for this decline is proposed to be related to improvement in nutritional status, environmental factors, heredity, and body mass index. Weight at birth of the child has also been considered to influence the onset of menarche.The aim of the study is to identify whether birth weight influenced the age of menarche in girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
0
2
Order By: Relevance
“…Our finding was supported by studies done by Raveendran RC et al, which also found no statistically significant correlation between birth weight and age at menarche. 26 However, our study was in contrast with studies done by by Steingraber which found that birth weight is a significant predictor of age at menarche. 1 Type of diet, especially intake of animal fat and protein has been proposed as a possible factor in determining age at menarche.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our finding was supported by studies done by Raveendran RC et al, which also found no statistically significant correlation between birth weight and age at menarche. 26 However, our study was in contrast with studies done by by Steingraber which found that birth weight is a significant predictor of age at menarche. 1 Type of diet, especially intake of animal fat and protein has been proposed as a possible factor in determining age at menarche.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are consistent with those of Raveendran RC et al, that there is no significant correlation was found between BMI and age of menarche. 26 Our study is also supported by Rao S et al, who challenged the critical weight hypothesis. 32 However our result is contrasting with several studies by Guo and Ji and Qing et al, which reported decrease in age at menarche with every unit increase in BMI.…”
Section: Discussionsupporting
confidence: 87%
“…As stated by Castilho SD et al [21] Gunther ALB et al [22], we also found no significant correlation between age of menarche and the type of diet (p=1.052). We found a significant correlation between BMI and age at menarche (p<0.05) which are inconsistent with Raveendran RC et al [23] and Rao S et al [24]& consistent with Guo et al [25] and Ji and Qing et al [26] who reported decrease in age at menarche with every unit increase in BMI.…”
Section: Discussioncontrasting
confidence: 85%